A modification method of recycled concrete aggregate and its application
Through the modification method of pretreatment, surface treatment and repair of recycled concrete aggregates, the problems of large porosity and high water absorption are solved, which significantly improves the mechanical properties, meets engineering needs, and realizes the sustainable development of green and environmentally friendly concrete.
Patent Information
- Application Number
- CN202311683085.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-12-08
AI Technical Summary
The existing recycled concrete aggregate has a large porosity, high water absorption, large stacking density and high crushing index, resulting in its mechanical properties lower than that of natural aggregates and cannot meet the actual engineering needs.
Modify the recycled concrete aggregate through three steps: pretreatment, surface treatment and repair. Pretreatment includes removal of steel bars, crushing, preheating, chilling, microwave heating and vibration grinding. Surface treatment includes the addition of a surface treatment agent, pressurization treatment, laser intermittent irradiation precipitation and inert gas filling. The repair step includes mixing with the compound bacterial solution and stirring and letting it stand to form a new mineral phase.
The apparent density and bulk density of modified aggregates are close to that of natural aggregates, with significantly lower water absorption and porosity, improved crushing indicators, significantly improved mechanical properties, meeting engineering needs, and achieving sustainable development of green and environmentally friendly concrete.
Smart Images

Figure BDA0004596870350000071 
Figure BDA0004596870350000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycled aggregates of building materials, and in particular to a modification method of recycled concrete aggregates and application thereof. Background Art
[0002] Concrete is the most widely used building material in the world. However, with the continuous acceleration of urbanization, the construction of new buildings and the demolition of old buildings have generated a large amount of construction waste, which accounts for 30%-40% of the total urban waste. However, only about 28% of construction waste is recycled each year, and the rest is landfilled or piled up, which not only occupies land resources, but also pollutes the environment and endangers human health. It is urgent to increase the resource utilization of construction waste. In recent years, the resource utilization of construction waste has received attention. It is processed into recycled aggregate and partially or completely replaces natural aggregate to prepare concrete. However, compared with natural aggregate, the current recycled aggregate from construction waste has more angular particles and a rough surface. Its components contain hardened cement mortar. During the crushing process, damage accumulates inside and causes a large number of microcracks, resulting in the recycled aggregate having the characteristics of large porosity, high water absorption, high bulk density, high crushing index, and high degree of surface inertness. A large amount of old cement mortar is attached to the surface of the recycled aggregate, with many surface pores and cracks, a weak interface transition zone (ITZ), and higher porosity and water absorption than natural aggregate. As a result, the mechanical properties of the recycled concrete prepared by it are lower than those of ordinary concrete and cannot meet the actual engineering needs.
[0003] At present, the modification measures for the surface strengthening of recycled aggregates mainly include: chemical solution infiltration strengthening, slurry filling strengthening, pre-absorption filling strengthening, physical shaping strengthening, in-situ strengthening, microbial strengthening, ultrasonic cleaning strengthening, high concentration carbon dioxide strengthening, etc. Physical strengthening technology can enhance the performance of recycled aggregates, but the current physical technology directly uses high-temperature calcination, which is easy to cause secondary damage to the recycled aggregates, resulting in fracturing, deterioration of the performance of the recycled aggregates, and there are problems such as large energy loss and high processing costs; chemical acid treatment can effectively weaken the mortar adhesion on the surface of the recycled aggregate, but it is easy to introduce Cl - 、SO 4 2- The current microbial enhancement has the advantages of being harmless and green, but most studies use a single bacterial community, and the composition of recycled aggregates is complex and changeable. The treatment effect of a single bacterial community may be insufficient. In addition, during the modification process, factors such as the temperature of the microbial growth environment, calcium ion concentration, pH value, bacterial concentration, and time will have a significant impact on the mineralization effect. It is difficult to achieve a better modification effect using only microbial treatment. Summary of the invention
[0004] In view of this, the present invention proposes a method for modifying recycled concrete aggregate to solve the above problems.
[0005] The technical solution of the present invention is achieved as follows: A method for modifying recycled concrete aggregate comprises the following steps:
[0006] S1. Pretreatment: Remove the steel bars from the construction waste, crush it to obtain recycled aggregate with a particle size of 20-80 mm, place it in an oven at 150-250° C. for preheating for 1-3 hours, take it out and place it in cold water for quenching, then place it in a microwave for 3-5 hours, take it out, add grinding media balls for vibration grinding to obtain particles with a particle size of less than 20 mm, sieve it, remove the old cement on the surface, and obtain aggregate I;
[0007] S2. Surface treatment: Add the above-mentioned aggregate I to the surface treatment agent and perform pressure treatment. The mass volume ratio of aggregate I to the surface treatment agent is 4-8:10. Maintain the pressure and infiltrate for 5-10 minutes. At the same time, fill with inert gas and perform intermittent laser irradiation precipitation. Each irradiation lasts for 10-30 seconds with an interval of 1-3 minutes. Take out and dry to obtain aggregate II.
[0008] S3. Repair: Mix aggregate II and the composite bacterial solution and stir evenly, spread the mixed aggregate on a tray, control the relative humidity to 60-80%, place it at 25-30°C for 10-14h, take it out, dry it, and obtain modified aggregate.
[0009] Furthermore, in said S1, the microwave temperature is 500-700°C, and the microwave power is 700-900W.
[0010] Furthermore, the grinding medium balls in S1 are one or a combination of zirconium oxide grinding medium balls, aluminum oxide grinding medium balls, zirconium silicate grinding medium balls or gravel.
[0011] Furthermore, the surface treatment agent of S2 comprises the following raw materials in parts by weight: 20-40 parts of acrylate, 10-18 parts of polyvinyl alcohol, 5-8 parts of sodium fluorosilicate, and 2-5 parts of calcium lignin sulfonate.
[0012] Furthermore, the pressure of the pressurization treatment in S2 is 10-15 MPa.
[0013] Furthermore, the laser energy density in S2 is 151-285 mJ / m 2 , wavelength is 248-335nm, frequency is 2-5Hz.
[0014] Furthermore, the inert gas in S2 is one of argon, xenon and helium, and the filling amount is 1.2-2.3 L / min.
[0015] Furthermore, the composite bacterial solution in S3 is prepared by mixing Pasteurella bovis, alkalophilic Bacillus H4 and Bacillus cohnii DSM6307 in a volume ratio of (2.2-2.9):(1.0-1.3):(0.2-0.9).
[0016] Furthermore, the effective bacterial content of the bovine Pasteurella is 2-4×10 7 CFU / g, the effective bacterial content of alkaliphilic Bacillus H4 is 1-3×10 7 CFU / g, the effective bacterial content of Bacillus cohnii DSM6307 is 3.2-5.8×10 7 CFU / g.
[0017] Furthermore, the modified aggregate obtained by the modification method of recycled concrete aggregate is used in concrete materials.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The invention modifies the construction waste by pretreatment, surface treatment and repair. The invention adopts a modification method combining physics, chemistry and biology. In the pretreatment process, the waste is preliminarily modified by a preheating + microwave heat treatment method to remove moisture in the regenerated aggregate. The heat energy provides activation energy to activate the ion exchange reaction in the aggregate. After the microwave treatment, the aggregate is more brittle but the performance of the aggregate is not degraded, which is beneficial to improving the strength and durability of the regenerated aggregate. The surface treatment agent is added and laser irradiation is used, so that the aggregate atoms obtain laser energy to promote crystal growth. At the same time, the surfactant penetrates into the interior of the aggregate to wrap the aggregate molecules, so that the interaction force between the molecules is stronger, the bonding strength is increased, the pore structure is refined, and the aggregate performance is improved. The invention utilizes the ability of microorganisms to decompose organic matter and minerals. The invention selects a specific composite bacterial liquid, which can effectively secrete calcium ions and silicate ions, react with substances on the surface of the regenerated aggregate, form a new mineral phase, change its internal structure, have a good filling effect, and effectively improve the density of the aggregate.
[0020] The modified aggregate of the present invention has been tested and its apparent density is 2.2-2.5 kg / m 3 , bulk density is 1.40-1.47kg / m 3 , water absorption is 3.26-4.18%, porosity greater than 200nm is 1.6-2.9%, and crushing index is 12.5-13.4; it has better apparent density and bulk density, and the water absorption and porosity greater than 200nm are significantly reduced. The apparent density and bulk density are equivalent to those of natural aggregate, and the water absorption and porosity are close to those of natural aggregate, thereby improving the utilization rate of recycled aggregate in concrete materials, realizing the sustainable development of green and environmentally friendly concrete, and promoting the large-scale application of recycled aggregate in the field of concrete. DETAILED DESCRIPTION
[0021] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0022] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0023] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0024] Example 1
[0025] A method for modifying recycled concrete aggregate comprises the following steps:
[0026] S1, pretreatment: remove the steel bars from the construction waste, crush it to obtain recycled aggregate with a particle size of 20 mm, place it in an oven for preheating at 150°C for 1 hour, take it out and place it in cold water for quenching, then place it in a microwave for 3 hours, the microwave temperature is 500°C, the microwave power is 700W, take it out, add grinding media balls for vibration grinding to obtain particles with a particle size of less than 20 mm, the grinding media balls are zirconium oxide grinding media balls, and sieve to obtain aggregate I;
[0027] S2. Surface treatment: The above-mentioned aggregate I was added to the surface treatment agent and pressurized at 10 MPa. The mass volume ratio of aggregate I to the surface treatment agent was 4:10 g / mL. The pressure was maintained and infiltrated for 5 minutes. At the same time, argon gas was filled and laser intermittent irradiation precipitation was performed. The laser energy density was 151 mJ / m 2 , wavelength of 248nm, frequency of 2Hz, irradiation for 10s each time, interval of 1min, take out, dry, and obtain aggregate II; the surface treatment agent includes the following raw materials in parts by weight: 20 parts of acrylate, 10 parts of polyvinyl alcohol, 5 parts of sodium fluorosilicate, and 2 parts of calcium lignin sulfonate;
[0028] S3, repair: Aggregate II and composite bacterial solution were mixed and stirred evenly. The composite bacterial solution was prepared by mixing bovine Pasteurella, alkaliphilic Bacillus H4 and Bacillus cohnii DSM6307 in a volume ratio of 2.2:1.0:0.2. The effective bacterial content of the bovine Pasteurella was 2×10 7 CFU / g, the effective bacterial content of alkaliphilic Bacillus H4 is 1×10 7 CFU / g, the effective bacterial content of Bacillus cohnii DSM6307 is 3.2×10 7 CFU / g, spread the mixed aggregate on a tray, control the relative humidity to 60%, place it at 25°C for 10 hours, take it out, dry it, and obtain the modified aggregate.
[0029] Example 2
[0030] A method for modifying recycled concrete aggregate comprises the following steps:
[0031] S1, pretreatment: remove steel bars from construction waste, crush to obtain recycled aggregate with a particle size of 80 mm, place in an oven for preheating at 250°C for 3 hours, take out and place in cold water for quenching, then place in microwave heating for 5 hours, microwave temperature is 700°C, microwave power is 900W, take out, add grinding media balls for vibration grinding to obtain particles with a particle size of <20 mm, the grinding media balls are alumina grinding media balls, sieve to obtain aggregate I;
[0032] S2. Surface treatment: The above-mentioned aggregate I was added to the surface treatment agent and pressurized at 15 MPa. The mass volume ratio of aggregate I to the surface treatment agent was 8:10 g / mL. The pressure was maintained and infiltrated for 10 minutes. At the same time, xenon gas was charged and laser intermittent irradiation precipitation was performed. The laser energy density was 285 mJ / m 2 , wavelength of 335nm, frequency of 5Hz, irradiation for 30s each time, interval of 3min, take out, dry, and obtain aggregate II; the surface treatment agent includes the following raw materials by weight: 40 parts of acrylate, 18 parts of polyvinyl alcohol, 8 parts of sodium fluorosilicate, and 5 parts of calcium lignin sulfonate;
[0033] S3, repair: Aggregate II and composite bacterial solution were mixed and stirred evenly. The composite bacterial solution was prepared by mixing bovine Pasteurella, alkaliphilic Bacillus H4 and Bacillus cohnii DSM6307 in a volume ratio of 2.9:1.3:-0.9. The effective bacterial content of the bovine Pasteurella was 4×10 7 CFU / g, the effective bacterial content of alkaliphilic Bacillus H4 is 3×10 7 CFU / g, the effective bacterial content of Bacillus cohnii DSM6307 is 5.8×10 7 CFU / g, spread the mixed aggregate on a tray, control the relative humidity to 80%, place it at 30°C for 14 hours, take it out, dry it, and obtain the modified aggregate.
[0034] Example 3
[0035] A method for modifying recycled concrete aggregate comprises the following steps:
[0036] S1, pretreatment: remove the steel bars from the construction waste, crush it to obtain recycled aggregate with a particle size of 50 mm, place it in an oven at 200°C for preheating treatment for 2 hours, take it out and place it in cold water for quenching treatment, then place it in a microwave for 4 hours, the microwave temperature is 600°C, the microwave power is 800W, take it out, add grinding media balls for vibration grinding to obtain particles with a particle size of less than 20 mm, the grinding media balls are zirconium silicate grinding media balls, and sieve to obtain aggregate I;
[0037] S2. Surface treatment: The above-mentioned aggregate I was added to the surface treatment agent and pressurized at 12 MPa. The mass volume ratio of aggregate I to the surface treatment agent was 6:10 g / mL. The pressure was maintained and infiltrated for 8 minutes. At the same time, helium was filled and laser intermittent irradiation precipitation was performed. The laser energy density was 212 mJ / m 2 , wavelength is 320m, frequency is 3Hz, irradiate for 20s each time, interval is 2min, take out, dry, and obtain aggregate II; the surface treatment agent includes the following raw materials by weight: 30 parts of acrylate, 15 parts of polyvinyl alcohol, 6 parts of sodium fluorosilicate, and 3 parts of calcium lignin sulfonate;
[0038] S3, repair: Aggregate II and composite bacterial solution were mixed and stirred evenly. The composite bacterial solution was prepared by mixing bovine Pasteurella, alkaliphilic Bacillus H4 and Bacillus cohnii DSM6307 in a volume ratio of 2.5:1.2:0.7. The effective bacterial content of the bovine Pasteurella was 3×10 7 CFU / g, the effective bacterial content of alkaliphilic Bacillus H4 is 2×10 7 CFU / g, the effective bacterial content of Bacillus cohnii DSM6307 is 4.2×10 7 CFU / g, spread the mixed aggregate on a tray, control the relative humidity to 70%, place it at 28°C for 12 hours, take it out, dry it, and obtain the modified aggregate.
[0039] Example 4
[0040] A method for modifying recycled concrete aggregate. The surface treatment agent comprises the following raw materials in parts by weight: 10 parts of acrylate, 22 parts of polyvinyl alcohol, 10 parts of sodium fluorosilicate, and 7 parts of calcium lignin sulfonate.
[0041] Example 5
[0042] A method for modifying recycled concrete aggregate. The composite bacterial solution is prepared by mixing bovine Pasteurella, alkaliphilic Bacillus H4 and Bacillus cohnii DSM6307 in a volume ratio of 1:1:1.
[0043] Comparative Example 1
[0044] The difference between this comparative example and Example 3 is that in the modification method of the recycled concrete aggregate, oven preheating and microwave heating are not performed, and calcination heating at 600° C. for 4 h is directly performed.
[0045] Comparative Example 2
[0046] The difference between this comparative example and Example 3 is that the composite bacterial solution is not used for repair in the modification method of the recycled concrete aggregate.
[0047] The specific steps include:
[0048] S1, pretreatment: remove the steel bars from the construction waste, crush it to obtain recycled aggregate with a particle size of 50 mm, place it in an oven at 200°C for preheating treatment for 2 hours, take it out and place it in cold water for quenching treatment, then place it in a microwave for 4 hours, the microwave temperature is 600°C, the microwave power is 800W, take it out, add grinding media balls for vibration grinding to obtain particles with a particle size of less than 20 mm, the grinding media balls are zirconium silicate grinding media balls, and sieve to obtain aggregate I;
[0049] S2. Surface treatment: The above-mentioned aggregate I was added to the surface treatment agent and pressurized at 12 MPa. The mass volume ratio of aggregate I to the surface treatment agent was 6:10 g / mL. The pressure was maintained and infiltrated for 8 minutes. At the same time, helium was filled and laser intermittent irradiation precipitation was performed. The laser energy density was 212 mJ / m 2 , wavelength is 320m, frequency is 3Hz, irradiate for 20s each time, interval is 2min, take out, dry, and obtain modified aggregate; the surface treatment agent includes the following raw materials in parts by weight: 30 parts of acrylate, 15 parts of polyvinyl alcohol, 6 parts of sodium fluorosilicate, and 3 parts of calcium lignin sulfonate.
[0050] Comparative Example 3
[0051] The difference between this comparative example and Example 3 is that in the repair of the modified method S3 of the recycled concrete aggregate, the aggregate II is directly immersed in the composite bacterial solution and immersed at 28° C. for 12 hours.
[0052] Comparative Example 4
[0053] The difference between this comparative example and Example 3 is that in the modification method of the recycled concrete aggregate, intermittent laser irradiation is not used for surface treatment.
[0054] S1, pretreatment: remove the steel bars from the construction waste, crush it to obtain recycled aggregate with a particle size of 50 mm, place it in an oven at 200°C for preheating treatment for 2 hours, take it out and place it in cold water for quenching treatment, then place it in a microwave for 4 hours, the microwave temperature is 600°C, the microwave power is 800W, take it out, add grinding media balls for vibration grinding to obtain particles with a particle size of less than 20 mm, the grinding media balls are zirconium silicate grinding media balls, and sieve to obtain aggregate I;
[0055] S2, surface treatment: add the above-mentioned aggregate I to the surface treatment agent and pressurize it at 12MPa, the mass volume ratio of aggregate I to the surface treatment agent is 6:10, maintain the pressure and infiltrate for 8 minutes, take out, and dry to obtain aggregate II; the surface treatment agent includes the following raw materials in parts by weight: 30 parts of acrylate, 15 parts of polyvinyl alcohol, 6 parts of sodium fluorosilicate, and 3 parts of calcium lignin sulfonate;
[0056] S3, repair: Aggregate II and composite bacterial solution were mixed and stirred evenly. The composite bacterial solution was prepared by mixing bovine Pasteurella, alkaliphilic Bacillus H4 and Bacillus cohnii DSM6307 in a volume ratio of 2.5:1.2:0.7. The effective bacterial content of the bovine Pasteurella was 3×10 7 CFU / g, the effective bacterial content of alkaliphilic Bacillus H4 is 2×10 7 CFU / g, the effective bacterial content of Bacillus cohnii DSM6307 is 4.2×10 7 CFU / g, spread the mixed aggregate on a tray, control the relative humidity to 70%, place it at 28°C for 12 hours, take it out, dry it, and obtain the modified aggregate.
[0057] Test Example 1-Performance Test
[0058] According to the relevant requirements and methods of national standards GB / T25176-2010 "Recycled fine aggregate for concrete and mortar" and GB / T25177-2010 "Recycled coarse aggregate for concrete", the recycled aggregates of Examples 1-5 and Comparative Examples 1-4 were tested for apparent density, bulk density, water absorption, porosity and crushing index, and the test results are as follows:
[0059]
[0060]
[0061] The results show that the aggregate modified by the present invention has better apparent density and bulk density than the unmodified aggregate, and the water absorption rate and porosity greater than 200 nm are significantly reduced. The apparent density and bulk density are equivalent to those of natural aggregate, and the water absorption rate and porosity are close to those of natural aggregate.
[0062] Compared with Comparative Example 1, the embodiment group can provide sufficient activation energy through preheating to activate the ion exchange reaction in the recycled aggregate, causing the expansion and connection of small cracks, improving its mechanical properties, and can also remove moisture in the recycled aggregate to make it drier, which is beneficial to improving the strength and durability of the recycled aggregate. In addition, the recycled aggregate after microwave treatment is in a completely brittle state, which is more conducive to the preparation of recycled concrete and prevents direct high-temperature calcination from causing aggregate fracturing or performance degradation;
[0063] Compared with Comparative Example 2, the composite bacterial solution induces calcium ion deposition, and the mineralization of the composite bacterial solution has a good filling effect on the pore structure of the recycled aggregate, effectively improving the density of the aggregate; the composite bacterial solution of the present invention can secrete calcium ions and silicate ions, react with substances on the surface of the recycled aggregate to form a new mineral phase, change the surface electrical properties and polarity of the recycled aggregate, thereby improving its bonding performance with cement slurry;
[0064] Compared with Comparative Example 3, the aggregate was immersed in the composite bacterial solution, and the effective bacteria in the composite bacterial solution floated on the upper layer, and the aggregate at the bottom could not be effectively and completely attached with the effective bacteria, which affected the mineralization effect of the aggregate;
[0065] Compared with Comparative Example 4, the inert gas is introduced and the laser is intermittently irradiated, so that the atoms in the aggregate obtain enough energy and begin to leave the equilibrium position, resulting in grain growth, which effectively improves the mechanical properties of the recycled aggregate, and can also promote the surface treatment agent to penetrate into the interior of the recycled aggregate, react chemically with the substances on the surface of the recycled aggregate to form a new covering layer, refine the pore structure, increase the density, and reduce the porosity. Subsequently, the properties of the transition zone between the recycled aggregate and the cement stone interface can be improved, and the interfacial bonding strength can be increased, thereby enhancing the overall performance of the concrete.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for modifying recycled concrete aggregate, characterized in that: The following steps are involved: S1. Pretreatment: Remove steel bars from construction waste, crush them to obtain recycled aggregate with a particle size of 20-80 mm, place them in an oven at 150-250° C. for preheating for 1-3 hours, take them out and place them in cold water for quenching, then place them in a microwave for 3-5 hours, take them out, add grinding media balls for vibration grinding to obtain particles with a particle size of less than 20 mm, and sieve them to obtain aggregate I; S2. Surface treatment: Add the above-mentioned aggregate I into a surface treatment agent and perform pressure treatment. The surface treatment agent comprises the following raw materials in parts by weight: 20-40 parts of acrylate, 10-18 parts of polyvinyl alcohol, 5-8 parts of sodium fluorosilicate, and 2-5 parts of calcium lignin sulfonate. The mass volume ratio of aggregate I to the surface treatment agent is 4-8:10 g / mL. Maintain the pressure and infiltrate for 5-10 minutes. At the same time, fill with inert gas and perform intermittent laser irradiation precipitation. The laser energy density is 151-285mJ / m 2 , wavelength 248-335nm, frequency 2-5Hz, irradiation 10-30s each time, interval 1-3min, take out, dry, get aggregate II, S3, repair: Aggregate II and composite bacterial solution are mixed and stirred evenly. The composite bacterial solution is prepared by mixing bovine Pasteurella, alkaliphilic Bacillus H4 and Bacillus cohnii DSM6307 in a volume ratio of (2.2-2.9):(1.0-1.3):(0.2-0.9), and the effective bacterial content of the bovine Pasteurella is 2-4×10 7 CFU / g, the effective bacterial content of alkaliphilic Bacillus H4 is 1-3×10 7 CFU / g, the effective bacterial content of Bacillus cohnii DSM6307 is 3.2-5.8×10 7 CFU / g, spread the mixed aggregate on a tray, control the relative humidity to 60-80%, place it at 25-30°C for 10-14h, take it out, dry it, and obtain modified aggregate.
2. The method for modifying recycled concrete aggregate according to claim 1, characterized in that: The microwave temperature in S1 is 500-700° C., and the microwave power is 700-900W.
3. The method for modifying recycled concrete aggregate according to claim 1, characterized in that: The grinding medium balls in S1 are one or a combination of zirconium oxide grinding medium balls, aluminum oxide grinding medium balls, zirconium silicate grinding medium balls or gravel.
4. The method for modifying recycled concrete aggregate according to claim 1, characterized in that: The pressure of the pressurization treatment in S2 is 10-15 MPa.
5. The method for modifying recycled concrete aggregate according to claim 1, characterized in that: The inert gas in S2 is one of argon, xenon and helium, and the filling amount is 1.2-2.3 L / min.
6. Application of a method for modifying recycled concrete aggregate, characterized in that: Application of modified aggregate obtained by the modification method of recycled concrete aggregate according to any one of claims 1 to 5 in concrete materials.
Citation Information
Patent Citations
Renewable concrete and preparation method thereof
CN110436837A
Cleaning and strengthening method for waste concrete recycled aggregate
CN110668727A